High-Energy-Density Sputtered Iridium Oxide Micro-Supercapacitors Operating in Physiological Electrolytes. Issue 5 (1st May 2022) - Geramifard, Negar; Chakraborty, Bitan; Dousti, Behnoush; Lee, Gil S.; Maeng, Jimin
Abstract : Traditional power sources for implantable devices, such as packaged internal batteries, suffer from bulkiness, limited cycle lifetime, and patient discomfort due to the need for periodic replacement surgery. Supercapacitors that directly utilize bodily fluids as electrolytes may serve as alternative power sources that are compact, durable, and patient-friendly. In this work, we present high-performance micro-supercapacitors that operate stably in physiological electrolytes for their potential as implantable miniature power sources. Sputtered iridium oxide films (SIROFs) produced using water-oxygen plasmas are employed as micro-supercapacitor electrodes and characterized in phosphate-buffered saline (PBS) and an inorganic model of interstitial fluid (model-ISF). The SIROF micro-supercapacitors exhibit a high volumetric capacitance of 425 F cm −3 (113 F g −1 ) in PBS and 223 F cm −3 (59.0 F g −1 ) in model-ISF, and an energy density of 59.1 mWh cm −3 (15.7 mWh g −1 ) in PBS and 30.9 mWh cm −3 (8.2 mWh g −1 ) in model-ISF. These devices show stability over 100, 000 charging-discharging cycles without loss of capacitance in these electrolytes. Polyethylene glycol coatings on SIROF are also investigated as a potential means of controlling biomolecule absorption and enhancing biocompatibility. This work provides a step toward implantable micro-supercapacitors that directly use the biological fluids as electrolytes.